2015
DOI: 10.1016/j.apmr.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Usability, and Cost-Benefit of a Virtual Reality–Based Telerehabilitation Program for Balance Recovery After Stroke: A Randomized Controlled Trial

Abstract: WB Saunders; ElsevierLloréns Rodríguez, R.; Alcañiz Raya, ML. (2015). Effectiveness, usability, and cost-benefit of a virtual reality-based telerehabilitation program for balance recovery after stroke: a randomized controlled trial. Sos Baynat s/n, Univesity of Jaume I, 12071 Castellón, Spain.Previous presentation of this material: no data have been presented before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
385
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(401 citation statements)
references
References 23 publications
9
385
1
6
Order By: Relevance
“…Istnieje potrzeba przeprowadzenia dużych badań motor function and body balance in chronic-phase stroke patients rehabilitated in hospital and at home was similar. At the same time, the cost of such intervention using tele-rehabilitation is significantly lower [23].…”
Section: Potencjalne Korzyści I Trudności Wyzwaniamentioning
confidence: 93%
See 1 more Smart Citation
“…Istnieje potrzeba przeprowadzenia dużych badań motor function and body balance in chronic-phase stroke patients rehabilitated in hospital and at home was similar. At the same time, the cost of such intervention using tele-rehabilitation is significantly lower [23].…”
Section: Potencjalne Korzyści I Trudności Wyzwaniamentioning
confidence: 93%
“…U pacjentów w przewlekłej fazie udaru rehabilitowanych w warunkach szpitalnych i domowych uzyskano podobną poprawę w zakresie funkcji lokomotorycznych i równowagi ciała. Jednocześnie koszt takiej interwencji w telerehabilitacji jest istotnie mniejszy [23].…”
Section: Potencjalne Korzyści I Trudności Wyzwaniaunclassified
“…We thank our colleague for the interest in our article 1 and the editors for the chance to clarify the text.…”
Section: The Authors Respondmentioning
confidence: 99%
“…(1,246 patients) of which were eligible for meta-analysis [9][10][11][16][17][18][19][20][21][22][23][24]. Figure 1 shows the details of our screening process.…”
Section: Study Selectionmentioning
confidence: 99%
“…After a meticulous full-text screening, 15 studies (1,339 patients) were identified as eligible for our systematic review [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24], 12…”
Section: Study Selectionmentioning
confidence: 99%